Efektivitas Psikoedukasi Melalui Musik terhadap Peningkatan Self Esteem Remaja Beresiko - Sasmita, Heppi; Tasman; Deviaroza; Rachmadanur, N; Muchtar, Murniati (LPPM Hang Tuah Pekanbaru, 2024)
The development of adolescence is very important throughout the life cycle. At this time, there is a change in adolescents' experience of fundamental physical and psychological. They also do not yet have effective coping experiences, causing difficulties in managing their emotions and behavior. The low self-esteem in adolescents causes them to be unable to maximize their potential. This study aimed to see an increase in self-esteem in at-risk adolescents by applying psychoeducation through music at SMPN 39 Padang. This quantitative study was designed in a